Norm and Numerical Radius Inequalities Related to the Selberg Operator - Altwaijry, Najla (2023)
The main focus of this paper is the study of the Selberg operator. It aims to establishappropriate bounds for the norm and numerical radius of the product of three bounded operators,with one of them being a Selberg operator. Moreover, it offers several bounds involving the summation of operators, notably the Selberg operator. Through the examination of these properties andrelationships, this study contributes to a better understanding of the Selberg operator and its influenceon operator compositions. The paper also highlights the significance of symmetry in mathematicsand its potential implications across various mathematical domains.